Motivational Teaching Strategies in Indonesian EFL Writing Classrooms - Yustinus Calvin Gai Mali (Celt: A Journal of Culture, English Language Teaching & Literature, 2017)
This qualitative study explores motivational teaching strategies employed in English as a foreign language (EFL) writing classrooms and designs a sample of lesson plans elaborating the strategies that were reflected from open-ended questionnaires of sixty-five first-year students at English Language Education Program in a private university in Indonesia. The data analysis reveals possible motivational strategies that are classified into Dornyei’s (2001) framework of motivational teaching practice. Based on the analysis, the study reinforces a view that teachers can motivate their students to learn and they use particular teaching strategies to motivate their students. Eventually, this study hopes to provide insights for EFL teachers espousing similar teaching practices, so they can enhance their students’ motivation, particularly in their EFL writing classrooms.